TUTUPAN TERUMBU KARANG KABUPATEN KOTABARU PROVINSI KALIMANTAN SELATAN (STUDI KASUS PERAIRAN SEPAGAR) - Deddy Dharmaji (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This research aims to know the percentage of living coral cover in the village of Sepagar. The benefits of this research are as input for the parties involved in the efforts of the management and conservation of coral reefs in the waters of the villageSepagar. The results of the observation and calculation of the coral reefs is done using the method of Point Intercept Trancek (PIT) shows that the community of coral reefsin the waters of the Sepagar included in the types of coral reefs of the sandbar (patchreef). Generally burnt coral reefs grow and develop in the relatively shallow waters with depths ranging from 1-5 meters. The results showed on the three stations found 7of the 10 components of the reef that is. Acropora (AC), Non-Acropora (NA), DeadCoral with Algae (DCA), Dead Coral (DC), Soft Coral Sand (SC) (S), and the Rubble(R). Component not found is Fleshy Seawed (FS), Rock (RK) and Silt (SL). At station1, the total percentage of living coral closure (living cover) by 51.4%, In station 2 of55,3 % , and in station 3 of 51.3 % .The percentage the coral lived in waters sepagar in good not far different the percentage the coral live in every station.